Prevalence of Diabetes Mellitus in Newly Diagnosed Tuberculosis Patients - Ajaykumar, Bandi; Tejolatha , Sabolu Sudeepa; Fazal, Mohammed; Vardhan, Nandigam Ashok (Journal of Neonatal Surgery, 2025)
Background: Tuberculosis (TB) and diabetes mellitus (DM) are significant global health challenges, with emerging evidence suggesting a bidirectional relationship between the two conditions. The coexistence of DM in TB patients can complicate treatment outcomes, increase relapse rates, and exacerbate disease severity. This study aims to determine the prevalence of diabetes mellitus in newly diagnosed tuberculosis patients and explore associated risk factors. Methods: A cross-sectional study was conducted among newly diagnosed TB patients at government multispecialty hospital, Sector 16, Chandigarh. Patients were screened for DM using fasting blood glucose, HbA1c, or random blood glucose tests as per WHO guidelines. Demographic data, clinical characteristics, and risk factors such as age, body mass index (BMI), family history of DM, and socioeconomic status were collected. Prevalence was calculated, and logistic regression analysis was used to identify factors associated with DM in TB patients. Results: In our study participants of 152 newly diagnosed TB patients, 21.7% were found to have diabetes mellitus. Among these, 6.5 % were newly diagnosed with DM, while 15.1 % had a prior DM diagnosis. Factors significantly associated with DM prevalence included older age showed high significance (p<0.001), higher BMI (p<0.05), and history of smoking (p<0.05). And there is a significant association that was observed with gender (p<0.35). Conclusion: The high prevalence of diabetes mellitus in newly diagnosed TB patients underscores the need for routine DM screening in TB management programs. Early detection and management of DM in TB patients could improve treatment outcomes and reduce complications. Further studies are warranted to assess the impact of integrated TB-DM care on long-term health outcomes.